Thromboprophylaxis of Patients with JAK2-Positive Myeloproliferative Neoplasms - Kimpton, Miriam (Université d'Ottawa / University of Ottawa, 2021)
Patients with JAK2-positive myeloproliferative neoplasms (JAK2MPN) form a rare patient population, at increased risk of arterial and venous thrombosis. Limited research is available to guide the thromboprophylaxis of these patients. Nonetheless, guidelines and expert opinions recommend the use of low-dose aspirin to decrease the risk of thrombotic complications. In order to build a research program on the thromboprophylaxis of JAK2MPN patients and assess the feasibility of conducting a randomized controlled trial comparing low-dose apixaban to low-dose aspirin for thromboprophylaxis in this patient population, we completed a systematic review and meta-analysis to provide reliable rates of thrombosis and bleeding on aspirin, we performed a survey of practice and a modified Delphi process to assess for heterogeneity in clinical practice and determine future research needs, and we developed a multi-centre, pilot randomized controlled trial on the feasibility of enrolling and retaining this patient population.
Keywords: Thromboprophylaxis; Myeloproliferative neoplams